If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + 25x = 105 Solving 30 + 25x = 105 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 25x = 105 + -30 Combine like terms: 30 + -30 = 0 0 + 25x = 105 + -30 25x = 105 + -30 Combine like terms: 105 + -30 = 75 25x = 75 Divide each side by '25'. x = 3 Simplifying x = 3
| x^2-12x+48=4 | | -3x+14=x-10 | | 12x+3y-(4x-2y)= | | M=10+-1m | | Cos(6x)+cos(4x)=o | | (1-3x)=0 | | 2x+5x=10x+60 | | 2A+10X^4C=0 | | 12x-3y-2(4x+y)= | | 2x-20=80 | | 7x+8y+3(2x+4y)= | | 5a+7a-6b-3a= | | 2(2n-3)=2n-2(n-1) | | m=4+m | | -5(-2x+3)= | | 7x-3y+9x-2y= | | Dx+9y=27 | | 5/8(x-7)=10 | | logv[12](x)+logv[12](11x-1)=1 | | 12x+5y=8400 | | 12x=6x+20-8 | | 5p+7s+4p-3s= | | 4x-32=9x+17 | | 15m^2-5m^2=30m+11m | | 7x+4y+2x-6y= | | 3x+7=5x-q | | 5x+12y=8400 | | 27=9s | | 10x-5=8x+15 | | (2x-3)/(5-3x)0 | | =(x+y-1)+(x+y+1)-(x+y-z) | | 4b-9b= |